First records of leucism in small rodents for Argentina - Beninato, Veronica A.; Rivero-Castro, Gustavo A.; Pérez, Mauricio A.; Borghi, Carlos E.; Giannoni, Stella M. (Therya Notes, 2020)
Leucism appears in various groups of vertebrates, although it is rare in mammals. For Argentina, we do not know of any documented registry for small rodents. The objective of our work is to report the first cases of leucism in cricetid rodents in the Puna Desert of Argentina. Field work was carried out in the Multiple Use Provincial Reserve Don Carmelo (San Juan, Argentina), located in the Puna Desert. The animals were captured in 9 grids formed by 36 Sherman-type traps, established in plots located between 3.100 and 3.300 m, in the years 2013-2014. We recorded 6 cases of leucism in 3 species of cricetids: Eligmodontia sp. (n = 3), Abrothrix andina (n = 2), and Phyllotis xanthopygus (n = 1). This work represents the first report of cases of leucism in small mammals from Argentina. The cases in the studied population could be due to the low gene flow imposed by the high environmental severity of an extreme desert, probably related to genetic causes derived from climatic and ecological factors, as these are non-anthropized environments.